Epiphyte orchid diversity in a Yungas montane forest in the Cotapata National Park and Integrated Management Natural Area, La Paz – Bolivia - Jiménez, Ivan (Universidad de Costa Rica, 2015)
In Bolivia the works focused on the study of the epiphyte vegetation are few and recent. This lack of knowledge is being filled by investigations like those of Ibisch (1996) about the flora and epiphyte vegeta- tion; Acebey & Krömer (2001), Acebey et al. (2003), Altamirano & Fernandez (2003) and Miranda (2005), who worked in the diversity and ecology of vascular and not vascular epiphytes.